Influence Analysis of Gross Domestic Product, Return on Equity, and Earning Share in Stock Price Using Moderating Variables Inflation over Consumer Goods Companies Indonesia Stock Exchange - Eki Anita; Dimas Angga Negoro (Penerbit Kemala Indonesia, 2019)
This research intends to examine macroeconomic factors and microeconomic factors that have affect stock prices, the variables studied are gross domestic product, Return on equity, and earnings per share of stock prices by moderating inflation in earnings per share of stock prices. In this study we analyze effect of gross domestic product, return on equity, and earnings per share, on stock prices and moderate inflation on earnings per share on stock prices, and can provide information and descriptions to investors able to evaluate the fair price of shares in a company based on variables in this research. Purpose sampling data collection techniques with the population used in this research were fifteen consumer goods companies that published financial statements and were listed on the Indonesia Stock Exchange from 2014 to 2018. Testing in this research was carried out with the help of the SPSS22 software program. The results showed that the variable return on equity and earnings per share both had positive and significant effects on stock prices while earnings per share moderated by inflation have a negative and significant effect on stock prices. But the gross domestic product variable is positive and has no significant effect on stock prices.